Do sales and service compete? The impact of multiple psychological climates on frontline employee performance. Issue 1 (2nd January 2017) - Ogilvie, Jessica; Rapp, Adam; Bachrach, Daniel G.; Mullins, Ryan; Harvey, Jaron
Abstract : This research examines how employees' climate perceptions – or psychological climate – influence their performance of climate-related outcomes. We focus on two specific climates arguably most relevant to boundary-spanning organizations: service and sales climates. Building from the resource-allocation framework, the authors examine the way employees reconcile these multiple psychological climates. Polynomial regression and response surface modeling are used to test for the influence of these distinct climates on employee outcomes using a sample of 252 marketing employees and their 68 immediate supervisors. Specifically, the authors examine relationships between service and sales climates and the employee performance outcomes of customer satisfaction, helping behavior, effort, and sales performance. Results provide insight into the benefits and pitfalls of sales and service climates co-existing. Specifically we find that while sales effort is highest in climates that heavily favor sales, sales performance may exist in both sales-favored and service-favored climates (yet not in the presence of both). From a customer satisfaction perspective we find no significant impact of increasing sales climate in the presence of high service perceptions. These findings – both significant and non-significant – provide implications for future research in the realm of service-sales ambidexterity and interface as well as insight and direction for frontline managers.